Chemoprevention of Experimental Periodontitis in Diabetic Rats with Silk Fibroin Nanoparticles Loaded with Resveratrol - Ana Giménez-Siurana; Francisco Gómez García; Ana Pagan Bernabeu; Antonio Abel Lozano-Pérez; Salvador D. Aznar-Cervantes; José Luis Cenis; Pía López-Jornet (MDPI AG, 2020)
Objective: the objective of the present work is to study the effectiveness of treatment with silk fibroin nanoparticles loaded with resveratrol in experimental periodontitis in a diabetic rat model. Introduction: Periodontitis is an inflammatory pathology highly related to other diseases, such as type II diabetes. Both diseases have a specific inflammatory condition, with Interleukin (IL)-6, IL-1β and Transforming Grow Factor (TGF)-1β being the most relevant proinflammatory factors. Silk fibroin (SF) nanoparticles loaded with resveratrol (Res-SFN) are a new alternative as a treatment. Methods: 40 diabetic Sprague Dawley male rats were used and periodontitis was induced by ligation. The animals were divided into 5 treatment groups, and 1 mL of treatment was administered once a day for 4 weeks. The groups were: I: Carboxymethyl cellulose (CMC) 0.8%, II: CMC 0.8% + SF 1%, III: CMC 0.8% + RES-SFN 3 mg/mL, IV: CMC 0.8% + SF 1% + RES-SFN 3 mg/mL, V: Water. A peripheral blood sample was taken every week to quantify the inflammatory profile by ELISA (IL-6, IL-1β and TGF-1β). After 4 weeks the sacrifice was carried out and biopsies of the gum were taken. Results: Treatment with SF and RES-SFN reduced the amount of chemical inflammation mediators (with the exception of IL-1β in comparisons I-IV and II-IV (p > 0.05)), as well as the anatomopathological variables linked to it, in a significant way (p < 0.05). Conclusion: treatment with RES-SFN has reduced local inflammation in this experimental periodontitis model.